Mild traumatic brain injury/concussion and female sexuality, a scoping review of the literature - Martina Anto-Ocrah; Kimberly Tiffany; Linda Hasman; Edwin van Wijngaarden (BMC, 2020)
Abstract Background The American Congress of Rehabilitation Medicine (ACRM) in 2010 called for more head injury research on gender disparities to bridge the gender gap for the short-and long-term effects of TBI, including sexual and reproductive outcomes. In this paper, we review the state of the literature before and after the ACRM announcement, and evaluate how research teams have considered females and mildly injured TBI(mTBI)/concussion groups in post-TBI-related changes in sexual functioning. Methods The research question for this scoping review was "what is the state of the literature in the evaluation of post-TBI sexual changes for women, and individuals with mTBI?" Using the 2010 ACRM call for action as a line of demarcation, we compared our findings before and after the 2010 announcement. Results We identified 9 research studies that addressed sexual functioning changes in females and mTBI/concussion groups. Four of the nine were published before the 2010 ACRM announcement, and five were published after. The representation of female research participants increased steadily over the 28-year timespan. The proportion of individuals with mTBI included in the post-2010 era was higher than the earlier time period. Consistently, women with mTBI reported more adverse sexual outcomes compared to male cohorts, orthopaedic, and non-injured comparison groups. This observation persisted regardless of recruitment site (rehabilitation center/Emergency Department (ED)/Community) or time of outcome assessment (acute versus chronic). The findings also remained despite the heterogeneity of survey questionnaires used to evaluate sexual functioning outcomes. Excluding the most recent 2019 study, none of the research groups compared the findings by TBI severity, making it difficult to fully understand how concussion-related sexual changes compare to more severe forms of the head injury. The long term impacts of the sexual changes, such as infertility and relationship discord were also absent across all studies; even though most evaluated outcomes chronically (some as far out as 20 years post injury). Conclusion The number of publications in the era before the ACRM call for action and afterwards were almost identical. In order to tailor interventions for the appropriate groups of TBI patients, more neurosexuality research is needed to increase awareness of the importance of sexuality as a health outcome for individuals with neurodisabilities.